Cultural and Regulatory Transformation of the Ministry of Religious Affairs: Eliminating Seniority, Breaking the Cycle of Violence in Islamic Boarding Schools - Muhamad Jamaludin (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
The rise in bullying cases in Islamic boarding schools indicates a systemic failure rooted in cultural, structural, and accountability issues. This phenomenon is exacerbated by a culture of seniority that normalizes violence as an initiation ritual and fuels a cycle of victimization and perpetration, where past victims replicate the violence after becoming seniors. Furthermore, limited safe reporting mechanisms and weak accountability of administrators who prefer amicable resolutions have perpetuated a culture of silence. This policy analysis uses a descriptive-analytical approach with qualitative methods, based on a literature review. Data were collected from written data references (academic journals, theses, and institutional reports) and regulatory support (Laws, Government Regulations, and PMA) in APA 7th Edition format. Problem identification was carried out through a Fishbone Diagram analysis, which groups the root causes into the categories of People, Systems, Culture, and Regulations. The assessment of policy alternatives (Regulation on Elimination of Hierarchy, Curriculum Integration, Independent Reporting System, Firm Sanctions, and Educator Certification) was conducted using William N. Dunn's Policy Alternative Scoring Theory, which focuses on the criteria of Effectiveness, Efficiency, Adequacy, Equity, and Responsiveness. The scoring results indicate that the Independent Victim Reporting and Protection System and Mandatory Integration of the Anti-Bullying Curriculum are the most feasible policy alternatives. Therefore, the main policy recommendation is the issuance of a Comprehensive Minister of Religious Affairs Regulation (PMA) which: 1) Requires the establishment of an Independent Anti-Violence Integrated Service Unit (ULT) in every Islamic boarding school (adopting the framework of TPPK PMA No. 73 of 2022); and 2) Compulsorily integrates the Positive Discipline and Anti-Bullying Curriculum. This policy aims to break the cycle of violence by replacing seniority control with professional supervision and guaranteeing full protection to students.